2012
DOI: 10.1021/ic301365y
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State and Time-Resolved Investigations on Pyrene-Based Chemosensors

Abstract: Two novel fluorescent probes bearing a single (P) and two (a podand-like structure, L) pyrene units derived from 1,5-bis(2-aminophenoxy)-3-oxopentane have been synthesized and investigated in dioxane using UV-vis absorption, and steady-state and time-resolved (in a picosecond time scale) emission spectroscopy; in the gas phase, matrix-assisted laser desorption ionization mass spectrometry was employed. In dioxane, the absorption and emission spectra of P present a unique band with maxima at 361 and 392 nm, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 74 publications
0
13
0
1
Order By: Relevance
“…Following our previous research with pyrene units [40], we have recently reported a single pyrene probe compound containing a fluorescent flexible dye [41]. Upon addition of metal ions, shows different colours from its yellow initial, such as, dark red for Cu 2+ , red orange for Zn 2+ and gold yellow for Ag + , thus allowing a direct visual differentiation and detection between these metal ions [41]. It is also worthy to report a recent study where an azide derivative of pyrene has shown to demonstrate a catalytic hydrolysis (to the aldehyde derivatives) upon addition of Hg 2+…”
Section: Accepted Manuscript M a mentioning
confidence: 99%
“…Following our previous research with pyrene units [40], we have recently reported a single pyrene probe compound containing a fluorescent flexible dye [41]. Upon addition of metal ions, shows different colours from its yellow initial, such as, dark red for Cu 2+ , red orange for Zn 2+ and gold yellow for Ag + , thus allowing a direct visual differentiation and detection between these metal ions [41]. It is also worthy to report a recent study where an azide derivative of pyrene has shown to demonstrate a catalytic hydrolysis (to the aldehyde derivatives) upon addition of Hg 2+…”
Section: Accepted Manuscript M a mentioning
confidence: 99%
“…This changes can be caused by different mechanisms such as photoinduced electron or charge transfer (PET or PCT) [6,7], excimer or exciplex formation [8][9][10], fluorescence resonance energy transfer (FRET) [11], internal charge transfer (ICT) [12,13], excited state intramolecular proton transfer (ESIPT) [14,15], etc [16]. 2+ ions has increasingly attracted the attention of several scientific fields [17] in particular medicine and environment [18].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Pyrene‐containing macromolecular structures have attracted a great deal of attention to be employed in fluorescent probes due to their long fluorescence lifetime and a well‐defined fluorescence spectrum, which is sensitive to the polarity of the environment . There are numerous studies in the literature on the fluorescence sensor applications of pyrene‐containing molecular compounds and high‐molecular polymers toward various analytes, including nitroaromatic compounds, metal ions, anions, and glucose …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] While some ionic species are essential to sustain growth, they may act as harmful pollutants in the environment. [ 4 ] As an example, compounds, [ 16,17 ] metal ions, [ 14,[18][19][20][21] anions, [ 22,23 ] and glucose. [ 24 ] Chemosensors are chemical compounds which can respond to the changes in their chemical environment when it binds to a guest counterpart by altering their electrical, electronic, magnetic, or optical signal.…”
Section: Introductionmentioning
confidence: 99%